DEVELOPMENT OF CHILDREN’S RELIGIOUS AND MORAL VALUES AT LIMITED OFFLINE LEARNING - Sujani, Elfara Hajjar; Ibrahim (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Religious and moral values are essential aspects of early childhood development. These aspects relate to children's character, behavior, and ability to recognize their religion. Schools have a significant role in stimulating children's religious and moral values. The children had time to do online-based learning due to the covid-19 pandemic. Now, children can do limited offline learning (PTM). The purpose of this study was to determine the differences in the development of children's religious and moral values during online learning and limited offline learning and to find out how significant the differences in the development of children's religious and moral values are during online learning and limited offline learning. The research method used is descriptive quantitative with ex-post facto design. The study was conducted at RA Al-Huda with a sample of 15 students in class A. The results showed differences in developing children's religious and moral values when online learning and limited offline learning were limited. The limited offline learning influences 57.9% of children's religious and moral values, and other factors influence 42.1%